Consequences of subtropical land-use intensity for the abundance and diversity of earthworm ecological categories - Xishuai Liu; Bingbing Wan; Dingyi Wang; Xiaoxu Qi; Yan Du; Jun Jiang; Xiaoyun Chen; Feng Hu; Manqiang Liu; Joann K. Whalen (Geoderma)
Understanding how soil biodiversity, especially of macrofauna like earthworms, responds to land-use intensity is crucial for developing sustainable land-use strategies. This work is a two-year field investigation of earthworm community responses to increasing land-use intensity, from undisturbed fallow land to actively cultivated agricultural lands (including fallow land, tea plantation, orange plantation, camphora plantation, synthetic fertilizer-amended cropland, compost-amended cropland, and vermicompost-amended cropland) in a subtropical region. Earthworm abundance and diversity increased with land-use intensity, likely due to the compensatory effects of organic amendments, which improve the habitat and resource availability, thereby alleviating the potential negative impacts of tillage and harvesting. Notably, earthworm abundance was higher in cropland (70 ind. m−2) than in other land-use types, such as fallow (4 ind. m−2) and plantation (22 ind. m−2). Greater earthworm abundance was associated with higher soil pH and more food resources, as indicated by high microbial biomass carbon (C), the humification index, and the particulate organic C fraction. Anecic and endogeic earthworms increased more than epigeic earthworms from fallow lands to plantations and croplands, reflecting their ecological adaptability to the soil conditions in managed lands with higher land-use intensity. This suggests that soil ecological restoration practices may enhance the role of earthworms related to soil structure dynamics and carbon sequestration. Our study provides empirical evidence that soil macrofauna have ecological adaptations to cope with agricultural intensification across landscapes.